PENGARUH ARUS KAS OPERASI, LABA SETELAH PAJAK, DAN PENGUKURAN ARUS KAS TRADISIONAL DALAM MEMPREDIKSI ARUS KAS MASA DEPAN (Studi Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Periode 2012-2016) - Amalia Yunika Putri, 13.05.52.0204; Sunarto, Sunarto (Students' Journal of Accounting and Banking, 2017)
This study aims to determine the effect of Cash Flow from Operation, Earnings After Tax, Earnings plus Depretiation and Amortization, and Working Capital to predicting Future Cash Flow at manufacture companies which listed in the Indonesia Stock Exchange. The population on this research is all manufacture company in the Indonesia Stock Exchange in 2012 - 2016. The sampling technique used was purposive sampling. The analytical tool was used is Multiple Regression Analysis. Partial results of this study show the Cash Flow from Operation and Earnings After Tax has a significant positive effect in predicting Future Cash Flows, while Earnings plus Depreciation and Amortization, and Working Capital from Operation are not influential in predicting future cash flows.Keywords: CFO, EARNS, EDPR, WCFO, Future Cash Flow